Community Empowerment through the Development of the Cisaat Tourism Village, Subang Regency - Willya Achmad; Hsiu. M Chuang; Uga Pratama Gunawan; Dini Nadila; Ikhsan Maulana (Yayasan Ilomata, 2023)
Cisaat Tourism Village's community empowerment is one way the village and government are helping locals make the most of their natural and human resources in order to better manage the tourism potential already present in the area. The purpose of this research is to detail how the growth of the Cisaat tourism village in Subang Regency, West Java, has facilitated a model of local community empowerment. This research uses a qualitative approach with descriptive methods. From the research, the community empowerment program in Cisaat village, Subang Regency, in general, has been going well, marked by the fulfillment of three aspects, namely the reach of access to empowerment, the level of community participation and supervision of tourist villages. This empowerment has been proven to provide benefits in improving the economy of rural communities, improving village development and increasing the human resources of local communities. There are obstacles faced in empowering the community, including the geographical condition of Cisaat Village which is prone to disasters, uneven human resource capacity and lack of concern for the surrounding environment.